Determinants of Land Technical Considerations in Land Control - Arnowo, Hadi (Sekolah Tinggi Pertanahan Nasional, 2023)
The significance of Technical Land Considerations (PTP) has grown in importance following the implementation of the Government Regulation replacing the Job Creation Law, particularly as an essential input for issuing Suitability of Spatial Utilization Activities (KKPR). Meanwhile, there are still many gaps in land use status that require effective monitoring activities. In order to effectively carry out land control, data and information regarding land control, ownership, and land use and utilization are required. PTP can be used as an effective land control instrument because it is an input to the issuance of KKPR and subsequently becomes a reference in land ownership applications. The effectiveness of PTP in land control is based on three factors that need to be properly applied: the presentation of the substance of PTP, PTP decisions, and PTP monitoring. PTP substances must be arranged in an accurate, objective, and up-to-date manner. PTP decisions must be informed by a comprehensive and thorough review and the impact of decisions on the community. Monitoring the outcome of the TPP decision is becoming a reference point for the continuation of the land ownership process. To ensure the ongoing issuance of PTP for various land activities, it is essential to incorporate the substance material of PTP into the records of land inspections. This integration facilitates the acquisition of comprehensive information that is pertinent to land ownership applications. In addition, the Land Office can anticipate problems with land tenure that is to be the subject of a land ownership application.